MGP regulates the adipogenic differentiation of mesenchymal stem cells in osteoporosis via the Ca2+/CaMKII/RIP140/FABP3 axis - Xinglang Wang; Yunhui Zhang; Chenhao Xu; Quanfeng Li; Pengfei Ji; Huatao Liu; Yibin Zhang; Jiahao Jin; Zihao Yuan; Miao Yuan; Pei Feng; Yanfeng Wu; et al. (Cell Death Discovery)
Abstract The dysregulation of bone marrow mesenchymal stem cells (BM-MSCs) is crucial in the pathogenesis of osteoporosis, and adipogenic differentiation of BM-MSCs is considered an essential factor in this process. However, the mechanisms underlying the regulation of MSC adipogenic differentiation require further investigation. MGP (Matrix Gla Protein) was reported to impair the osteogenic differentiation. However, the mechanisms through which MGP regulates osteoporosis and bone-fat imbalance in MSCs are still unclear. In this study, we confirmed that the expression of MGP upregulated in osteoporosis and has a negative correlation with BMD (bone mineral density). Gain- and loss-of-function experiments were performed to ensure the role of MGP in MSC adipogenic differentiation. Mechanistically, MGP increased intracellular free Ca2+ levels and enhanced CaMKII phosphorylation, which in turn activated RIP140 protein degradation. This led to an increase in the transcription of FABP3, ultimately promoting adipogenic differentiation in MSCs. Furthermore, we demonstrated that using recombinant adeno-associated virus 9 (rAAV9) to silence MGP has the effect of alleviating bone loss and reversing the excessive bone marrow adipose tissue in mice with osteoporosis. In summary, our research has unveiled the regulatory role of MGP/Ca2+/CaMKII/RIP140/FABP3 axis in adipogenic differentiation in MSC and it might be a promising approach for osteoporosis treatment.